Education on the Effect of Price Perception on Consumer Purchasing Decisions - Lestari, Fitriani; Dayana, Nurul Aida; Puspita, Mutia Dila; Harahap, Muhammad Ikhsan (Proceeding International Conference on Islamic Economics Community Services (ICIECS), 2023)
The rapid economic growth in Indonesia, especially in the retail sector, has affected the consumption patterns of people in big cities such as Medan. This article examines the influence of price perception on consumer purchasing decisions at Swalayan Grosir Indah, a minimarket chain that provides a variety of basic needs. This research uses Deep Interview, Training, and Participatory methods to understand consumers' perceptions of price and determine effective pricing strategies. The results show that discounts have a significant influence on consumer purchasing decisions. Discounts offered provide immediate benefits that increase consumers' attractiveness and motivation to make purchases, while promotions also play an important role although not as big as discounts. Fair and transparent pricing contributes to increased consumer satisfaction and loyalty, and encourages repeat purchases. The findings provide valuable insights for retail businesses in formulating pricing strategies that can improve consumer satisfaction and purchase decisions.